2022
DOI: 10.3390/foods11193010
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Properties of Zein, Soy Protein Isolate, and Wheat Gluten Protein-Based Films Containing Cellulose Nanocrystals

Abstract: Plant protein films are a research hotpot in the current food packaging field for their renewable and bio-compatibility, and further improving the physicochemical properties of plant protein films in combination with biodegradable materials is of great significance. In this study, we selected cellulose nanocrystals (CNC) to modify the protein films with soybean protein isolate (SPI), wheat gluten protein (WGP), and Zein, and the physicochemical properties were studied. The results showed that the hardness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In another work, Fu et al used cellulose nanocrystals (CNCs), SPI, wheat gluten protein (WGP), and zein to construct protein membranes and explored their physicochemical properties (Figure 7c). 68 The results showed that the SPI-based films had lower hardness and higher tensile strength. After addition of CNC, the hardness and opacity of zein-based films decreased by 16.61% and 54.12%, respectively.…”
Section: Protein and Itsmentioning
confidence: 97%
See 2 more Smart Citations
“…In another work, Fu et al used cellulose nanocrystals (CNCs), SPI, wheat gluten protein (WGP), and zein to construct protein membranes and explored their physicochemical properties (Figure 7c). 68 The results showed that the SPI-based films had lower hardness and higher tensile strength. After addition of CNC, the hardness and opacity of zein-based films decreased by 16.61% and 54.12%, respectively.…”
Section: Protein and Itsmentioning
confidence: 97%
“…(c) Schematic diagram of the preparation of different plant protein membranes. Reprinted or adapted with permission under a Creative Commons (CC BY 4.0) from Figure 1 in ref . Copyright 2022, MDPI.…”
Section: Agriculture Mulch From Degradable and Renewable Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the protein-based film also may provide nutrients, particularly zein which is considerably less allergic compared with other commonly used proteins (such as casein, soy protein, and wheat gluten) (Luís et al, 2019). The mechanical properties of zein-based film also exhibit excellent features compared with other plant protein-based film such as soy protein isolate and wheat gluten protein (Fu et al, 2022). However, the zein-based film exhibited brittle film and stiffer in the mixture.…”
Section: Introductionmentioning
confidence: 99%